Pengembangan Media Kongkrit Pada Pembelajaran Matematika Materi KPK dan FPB Kelas IV SD Inpres Maccini Baru Kota Makassar - Sri Astuti; Nasrun Nasrun; Ernawati Ernawati (STIKes Ibnu Sina Ajibarang, 2023)
The problem in this research was the discovery of problems in the learning process, where students had minimal understanding regarding the material presented by the teacher. This research aims to determine whether concrete media development can influence students' interests, attitudes and abilities in absorbing information from the material presented by the teacher. This type of research is research and development (R&D) which aims to determine the validity and practicality of a concrete learning media in the form of congklak for fourth grade students at SD Inpres Maccini Baru, Tamalate District, Makassar City. The development model used is the ADDIE model consisting of analysis, design, development, implementation and evaluation stages. The subjects in this research were 32 grade IV students at SD Inpres Maccini Baru, Tamalate District, Makassar City. The data collection technique was carried out by means of a questionnaire. The results of the validity and practicality that were developed were a media validity percentage of 81.6% with the